1985
DOI: 10.1111/j.1467-8624.1985.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Auditory Temporal Acuity in Children

Abstract: The development of auditory temporal acuity was studied in 56 children aged 6-12 years and compared with that of 8 adults. Acuity was measured by determining the minimum detectable duration of a brief cessation in a noise band with the 2-alternative forced-choice method. For detection of gaps in a broadband noise, acuity improved significantly with age and reached adult values by 11 years. The minimum detectable duration was significantly shorter at higher levels of the noise. For narrow-band noises, acuity al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
5
12

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 21 publications
9
62
5
12
Order By: Relevance
“…This was quantified in terms of the difference between thresholds in the steady-low and the minimum threshold in the AM masker, in terms of the range of thresholds observed in the AM masker, and in terms of the ERD based on fits to the wideband masker data. This result is broadly consistent with previous results showing a developmental effect in tasks relying on temporal resolution (Irwin et al, 1985;Wightman et al, 1989;Grose et al, 1993;Hall and Grose, 1994), including studies of non-simultaneous masking (Hartley et al, 2000;Hill et al, 2004). Further, for the wideband masker data, there was relatively more backward than forward masking in the youngest listeners tested, confirming the non-significant trends observed by Buss et al (1999).…”
Section: A Temporal Resolution As a Function Of Agesupporting
confidence: 82%
See 1 more Smart Citation
“…This was quantified in terms of the difference between thresholds in the steady-low and the minimum threshold in the AM masker, in terms of the range of thresholds observed in the AM masker, and in terms of the ERD based on fits to the wideband masker data. This result is broadly consistent with previous results showing a developmental effect in tasks relying on temporal resolution (Irwin et al, 1985;Wightman et al, 1989;Grose et al, 1993;Hall and Grose, 1994), including studies of non-simultaneous masking (Hartley et al, 2000;Hill et al, 2004). Further, for the wideband masker data, there was relatively more backward than forward masking in the youngest listeners tested, confirming the non-significant trends observed by Buss et al (1999).…”
Section: A Temporal Resolution As a Function Of Agesupporting
confidence: 82%
“…Studies have shown that children perform more poorly than adults on a range of temporal resolution tasks, including gap detection (Irwin et al, 1985;Wightman et al, 1989;Trehub et al, 1995), amplitude modulation detection (Hall and Grose, 1994), and detection of a brief tone presented before or after a noise masker (e.g., Buss et al, 1999;Hartley et al, 2000). Some data indicate that the maturation of temporal processing may be frequency specific (Irwin et al, 1985;Grose et al, 1993;He et al, 2010). For example, He et al (2010) measured tone detection thresholds for a range of signal durations in school-aged children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, gap detection is influenced by attention and intensity coding (Irwin et al 1985;Wightman et al 1989;Werner et al 1992;Buss et al 2012). The current study used the temporal modulation transfer function (TMTF) to separate temporal resolution from non-temporal factors using the method introduced by Viemeister (1979).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The auditory ability for temporal resolution is the minimum time required for separating or resolving acoustic events. 8,9 In trying to locate the physiological mechanism of temporal resolution, some authors have suggested that auditory nerve fibers participate significantly in the process. 5,10,11 Other studies, however, have shown that processing is more central.…”
Section: Introductionmentioning
confidence: 99%